Эффективность отраслевой науки: измерение и стимулы / Шелудько Л. Г. - Шелудько Л. Г. (Экономика, 1991)
Экземпляры: КХ (20100827) / Инвентарный номер: 992927 / Цена: 0.50 / Сис.шифр: 65.9(2) / Авт.знак: Ш 44 / ГРНТИ: 26 / ББК: 65.497.2